Investigação química, embriotoxicidade em peixes-zebra (Danio rerio) e atividades antimicrobiana e antibiofilme de Leonotis nepetifolia (L) R. Br - Adolpho, Luciana de Oliveira (2022)
Leonotis nepetifolia, popularly known as cord-de-frade, is a plant of African origin, naturalized in the state of Rio Grande do Sul. This species is used in popular and Ayurvedic medicine for the treatment of various illnesses, such as diabetes, fever, cough, skin infections, kidney problems, inflammation, among others. Among the proven biological activities are antifungal, antibacterial, antitumor, antioxidant, anti-nociceptive and anti-inflammatory activities, and most of these studies with the leaves of L. nepetifolia. The flowers of this plant, in addition to being used in popular medicine, are consumed in Mexico, replacing Cannabis. Despite its widespread use, there are still few studies regarding the phytochemical composition of flowers, as well as the toxicity of this plant. In this sense, this study aimed to obtain essential oils, extracts and fractions of aerial parts of L. nepetifolia, perform the characterization of the chemical composition, evaluate the antimicrobial, antimycobacterial, antibiofilm activity and toxicity in embryos of Danio rerio (zebrafish). Analysis by gas chromatography coupled to mass spectrometry (GCMS) of essential oils from leaves and flowers indicated that germacrene D, b-caryophyllene, a-caryophyllene and b-elemene are major metabolites common to both oils. Both the essential oils and the extracts and fractions showed a broad spectrum of microbial inhibition, with a MIC of 125 to 250 µg.mL1, highlighting the inhibition of mycobacteria, M. abscessus , M. massiliense and M. fortuitum, with a MIC of 359, 57 µg.mL1 for all samples tested, with the exception of CEL. The ethyl acetate fractions of the leaves and flowers at a concentration of 31,25 µg.mL1 were effective in decreasing the biofilm formation of K. pneumoniae in 61,82% and 40%, respectively. In addition to the inhibition of biofilm formation, leaf fractions were effective in disrupting the preformed biofilm of K. pneumoniae. The antioxidant activity by the DPPH method indicated that the ethyl acetate fraction of the flowers had the best antioxidant capacity - with an IC50 of 302.18 µg.mL1. The phytochemical study was carried out through chromatographic techniques, where it was possible to isolate the compounds: phytyl palmitate, stigmasterol, b-sitosterol, nepetifoliol, glunol, linoleic acid, palmitic acid, ellagic acid, verbascoside, b- glycosylated sitosterol and isomaltulose, which were characterized by GC-MS, NMR and HRMS. The substances present in n-hexane fractions were identified by GC-MS, including campesterol, glutinol, a-amyrin, b-amyrin, cycloartenol acetate, spathulenol, phytol, squalene, campesterol, among others. In addition, the analysis by UHPLC-ESI-HRFTMS of the ethyl acetate fractions of the flowers was carried out, through dereplication, comparing the molecular form of each identified substance, with phytochemical substances already reported for the genus or family, allowing the recording of 96 substances present in ethyl acetate fraction of flowers, among them, verbascoside was noted as the major peak. The ethyl acetate fraction of the leaves showed the flavonoid cirsiliol as the major compound. The test of acute toxicity in embryos of Danio rerio, demonstrated that the samples belonging to the flower of L.nepetifolia were the ones that presented greater toxicity, high lethality rate, delays in hatching and the presence of malformations .